Estudo dos genes relacionados a mecanismos de reparo em danos de DNA em síndrome mielodisplásica - Ribeiro Júnior, Howard Lopes (2013)
Myelodysplastic Syndrome (MDS) is a group of diseases of clonal hematopoietic progenitor cells, characterized by cytopenia (s) peripheral (s), dysplasia of one or more myeloid cell lineages and increased risk for development of acute myeloid leukemia. MDS is considered a disease of older people, because approximately 80% of patients have more than 60 years at diagnosis. Are rare in children, being observed in less than 5% of hematologic malignancies that affect patients under 14 years of age. The pathogenesis of MDS involves DNA damage in hematopoietic stem cells probably affected by Double-Strand Break (DSB) in the process of Non-homologous end join (NHEJ) and homologous recombination (HR) repair mechanisms as key for ensuring genomic stability of cells trunk. This cohort study proposed evaluate the association between rs4793191, rs9567623 and rs1801320 polymorphisms of the BRCA1, BRCA2 and RAD5 genes, acting on the HR mechanism; the rs3835, rs2267437 and rs1805388 of the XRCC5, XRCC6 and LIG4, related with NHEJ mechanism and, finally, ATM rs228593 as molecular sensor damage in DSBs. This genotyping analysis was based on the methodology of PCR-RFLP, between bone marrow samples of 60 patients with MDS, from the University Hospital Walter Cantidio, and 82 peripheral blood samples of elderly healthy volunteers with approval in the CEP / HUWC under protocol No. 027.04.12. The MDS patients were diagnosed by examination of bone marrow and bone marrow cytogenetic analysis technique by G band. The genotypes studied polymorphisms were in Hardy-Weinberg equilibrium (p> 0.05), except for the rs1805388 polymorphism in LIG4 gene. Our results showed for the rs228593 polymorphism of the ATM gene association with low-risk MDS for genotype A /G (p = 0.008, OR 0.225, CI 0.075 to 0.680) with added association of genotype A/G with the clinical variables of cytopenia (p = 0.032, OR 5.250, CI 1.151 to 23.937), in the range of 0-1 in peripheral blood cytopenias, and with favorable prognosis in IPSS (p <0.001, OR 21.95, CI 29.791 to 16.185). For the rs2267437 polymorphism in the gene XRCC6 relate the mutant genotype C / C and G / G + G / G with variable marrow cellularity in the range of normocellular + hypercellular (p = 0.023, OR 5.556 CI 1.270 to 24.239). For the genotypes of rs3835 polymorphism of the XRCC5 gene identify the genotype A / G is highly associated with low-risk MDS (p <0.001, OR 0.100, CI 0.035 to 0.289). Additionally, for the rs1801320 polymorphism of the gene RAD51, we associate the mutant heterozygous genotype G/C with low-risk MDS (p = 0.053, OR 0.453, CI 0.203 to 1.009). For the same polymorphism, we associate the wild genotype G / G with variable age (p <0.001, OR 24.521, CI 64.033 to 93.907), in the range of greater than 60 years old, and with the variable cytopenia (0-1 cytopenias) (p <0.001, OR 16.099, CI 31.299 to 82.808). We did not obtain significant association between polymorphisms rs 4793191, rs9567623 and rs1805388 for the genes BRCA1, BRCA2 and LIG4, respectively, and clinical variables for patients with MDS. In this study we demonstrate that genes related to DSB are also related to the pathogenesis of MDS. These results support the importance of polymorphisms rs228592, rs3835, rs2267437 and rs1801320 in the ATM, XRCC5, XRCC6 and RAD51 genes, respectively, in the maintenance of genomic stability by promoting a better understanding of the genesis and etiology of myelodisplastic syndrome.